KEABSAHAN PERJANJIAN ELEKTRONIK PENYEDIA LAYANAN UANG DIGITAL: ( Studi Kasus Hilangnya Uang di Aplikasi Dana ) - Bagas Tri Mahesa (CV. KAMPUS AKADEMIK PUBLISING, 2023)
. The rapid development of information technology has led to major changes in the way people conduct transactions, including the making of contracts such as electronic contracts. From the perspective of contract law, electronic contracts are essentially subject to the same principles as ordinary contract agreements. Electronic contracts must still meet the legal requirements of a contract: agreement between the parties, capacity or lack of capacity of the parties, certain goods that have been predetermined, and goods that are not prohibited. Problems that often arise in electronic contracts are regarding the validity of law, contract evidence, and electronic signatures. The lack of physical documents and signatures makes it difficult to determine the intentions of the parties and the validity of the contract. The Electronic Information Transactions Law (UU ITE) regulates the validity and legal consequences of electronic contracts. UU ITE recognizes electronic signatures as a legal tool for concluding contracts. However, the validity and other technical requirements of electronic contracts made by electronic agents (artificial intelligence) are still under debate. The case of sudden loss of money in the Dana application can lead to legal problems for both Dana users and Dana as a service provider. From the perspective of contract law, sudden loss of money can be considered a breach of contract or an illegal act committed by OJK. Therefore, the cases discussed here require a comprehensive understanding of electronic contracts from the perspective of contract law. This study provides a deep analysis of the legal requirements, evidence, and legal consequences of electronic contracts, as well as the challenges and solutions related to the loss of funds in fund applications.